2008
DOI: 10.1007/s10680-008-9162-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Individuals’ Desired Family Sizes Stable? Evidence from West German Panel Data

Abstract: Using West German panel data constructed from the 1988 and 1994/ 1995 wave of the DJI Familiensurvey, we analyze the stability and determinants of individuals' total desired fertility. We find considerable variation of total desired fertility across respondents and across interviews. In particular, up to 50% of individuals report a different total desired fertility across survey waves. Multivariate analysis confirms the importance of background factors including growing up with both parents, having more siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
112
3
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 61 publications
14
112
3
9
Order By: Relevance
“…In contrast, Axinn, Clarkberg, and Thornton (1994) found, with US data, that the number of children a mother had borne had a positive influence on the family size preferences of their children at age 18. Heiland, Prskawetz, and Sanderson (2008) reported a positive influence of the number of siblings on the ideal family size of childless women under the age of 35 in Germany based on data from 1988and 1994. Régnier-Loilier (2006 came to a similar conclusion with a French sample of men and women ages 15-45 conducted in 1998: The more siblings the respondent had, the higher the desired number of children.…”
supporting
confidence: 60%
“…In contrast, Axinn, Clarkberg, and Thornton (1994) found, with US data, that the number of children a mother had borne had a positive influence on the family size preferences of their children at age 18. Heiland, Prskawetz, and Sanderson (2008) reported a positive influence of the number of siblings on the ideal family size of childless women under the age of 35 in Germany based on data from 1988and 1994. Régnier-Loilier (2006 came to a similar conclusion with a French sample of men and women ages 15-45 conducted in 1998: The more siblings the respondent had, the higher the desired number of children.…”
supporting
confidence: 60%
“…Some studies have documented that highly educated women are more likely than their less educated counterparts to say they want to have or are planning to have a large family (e.g., Heiland et al 2008;Mills et al 2008); while other studies have found that better educated women have lower completed fertility levels than less educated women. These apparent discrepancies suggest that unplanned births or early childbearing are the reasons for the higher fertility levels among less educated women (e.g., Musick et al 2009;Hayford 2009;Hayford and Guzzo 2016).…”
Section: Education and Reproductive Plansmentioning
confidence: 99%
“…This issue has been addressed in two recent papers: Heiland et al (2008) and Liefbroer (2008). However, both these papers are based on models which conceptualise downward revisions in fertility intentions as equal and opposite to upward revisions -and which therefore constrain the determinants of upward and downward revisions to be equal and opposite.…”
Section: Introductionmentioning
confidence: 99%
“…However, there also exist studies based on longitudinal data which demonstrate clearly that individuals revise their fertility intentions over their lives. Studies by Westoff and Ryder (1977), Monnier (1989), Berrington (2004), Heiland et al (2008), Liefbroer (2008) and Hayford (2009) are based on samples taken at different times and from different countries; they share the finding that people do change their fertility intentions, and that while downward adjustments are more frequent than upward adjustments, adjustments in both directions are common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation